Introducing Negatively Charged Residues on the Surface of Fetal Hemoglobin Improves Yields in Escherichia coli - Kettisen, Karin; Bülow, Leif (Frontiers in Bioengineering and Biotechnology, 2021)
Fetal hemoglobin (HbF) has been developed into an important alternative protein for oxygen therapeutics. Such applications require extensive amounts of proteins, which only can be achieved via recombinant means. However, the expression of vertebrate hemoglobins in heterologous hosts is far from trivial. There are several issues that need to be dealt with. These include, among others, the solubility of the globin chains, equimolar expression of the globin chains, and access to high levels of free heme. In this study, we examined the impact of introducing negative charges on the surface of HbF. Three different HbF mutants were examined, carrying four additional negative charges on the α-subunit (rHbFα4), two additional negative charges on the γ-subunit (rHbFγ2) or a combination of these (rHbFα4/γ2). The increase in negative surface charge in these HbF mutants required the development of an alternate initial capture step in the downstream purification procedures. For the rHbFα4 mutant, we achieved a significantly enhanced yield of purified HbF with no apparent adverse effects on Hb functionality. However, the presence of non-functional Hb portions in the rHbFγ2 and rHbFα4/γ2 samples reduced the yields significantly for those mutants and indicated an imbalanced expression/association of globin chains. Furthermore, the autoxidation studies indicated that the rHbFγ2 and rHbFα4/γ2 mutants also were less oxidatively stable than rHbFα4 and wt rHbF. The study further verified the need for an improved flask culture protocol by optimizing cultivation parameters to enable yield-improving qualities of surface-located mutations.